Kelainan amatan tentang kebolehterjemahan: Kes bahasa Cina kepada bahasa Malaysia - Goh, Sang Seong; Mashudi Kader (Universiti Kebangsaan Malaysia, 2008)
This article analyses the differences in a translators perception on translatability and its effect on the retention of the source message in translations of Chinese language to the Malay language. Fifty linguistic cultural items from the Malay translation of Shui Hu Zhuan have been used as the corpus of this analyses. A questionnaire containing fifty linguistic-cultural forms was administered to a group of students of translating programme and who are proficient in both Mandarin and Malay. A simple quantitative and qualitatif analysis on the feedbacks shows that the differences in the perception of the concept of translatability between the one that is held by the reseachers and that of the second-raters prove to be the main source of varieties of translation outputs. The principal messages of the target texts are not grossly different between those produced by individuals whose perception of translatability are not the same